ANALYSIS OF MAGNETIC FLUX DISTRIBUTION IN NONLINEAR MAGNETIC CIRCUITS WITH DISTRIBUTED PARAMETERS AND A MOVABLE CORE USING THE RUNGE–KUTTA METHOD (International Conference on Economics, Finance, Banking and Management, 2025)
The article presents the nonlinear differential equations characterizing the parameters of the processes in a nonlinear magnetic circuit with a distributed parameter and a movable core. These equations are solved using the Runge–Kutta method. The obtained solutions are compared with experimentally measured values, and the relative errors are determined. Considering the small magnitude of the errors and the fact that exact analytical solutions for nonlinear differential equations do not exist, it is proven that applying the numerical Runge–Kutta method is an effective approach to finding solutions.